Oxygenation index and NT-proBNP as predictors of pulmonary hypertension and ventilation/perfusion mismatch in acute pulmonary embolism - Ye, Wenjing; Chen, Xi; Li, Xiaoming; Guo, Xuejun; Gu, Wen (Frontiers in Cardiovascular Medicine, 2023)
Introduction: The magnitude of pulmonary artery pressure (PAP) and the extent of ventilation/perfusion (V/Q) mismatch are essential for assessing the prognosis of acute pulmonary embolism (APE). We aimed to develop a model for predicting the status of the pulmonary circulation and arterial gas exchange functions using serum levels of cardiac biomarkers and arterial oxygenation index (OI) values. Materials and Methods: This single-center, retrospective observational cohort study included 224 patients with APE. Multivariate linear regression and Poisson regression were used to test the statistical association between cardiac biomarkers, OI, PAP, and V/Q mismatch. Diagnostic efficiency was calculated from a receiver operating characteristic (ROC) curve. Results: Serum levels of troponin I (TNI), N-terminal pro-brain natriuretic peptide (NT-proBNP), and arterial OI magnitude significantly correlated with PAP and V/Q mismatches (P<0.05). Multivariate linear regression showed that NT-proBNP serum levels (β=0.002, P<0.001) and OI values (β=–0.022, P=0.001) significantly influenced PAP. Arterial OI (β=–0.039, P<0.001) had a significant influence on the percentage of pulmonary vascular obstruction (PVO) as determined by perfusion scanning. Poisson regression showed that OI (odds ratio: 0.995, p<0.001) was a predictor of the number of lung segments with V/Q mismatches. ROC area under the curve (AUC) values of NT-proBNP and OI predicting pulmonary hypertension were 0.716 and 0.730 respectively, and for V/Q mismatch scanning, the results were 0.601 and 0.634, respectively. Conclusions: Arterial OI and serum levels of cardiac biomarkers may be used as indicators of pulmonary hypertension and V/Q mismatch.